(untitled) (Italian Journal of Public Health, 2009)
Background: The Slovak Republic joined the European Union (EU) on May 1st 2004. The public health system of the country is under continuous transition including public health education and training. The aim of the presented paper is to describe and discuss how far the transition of public health education of the country went during last time period. Methods: Web site review, documentation search and curriculum content analysis were the main methods employed within presented paper. Results: There are 7 universities offering public health education on bachelor, master and doctoral level. Among them 6 could be found in list of accredited universities of the Ministry of Education by Accreditation Committee of the Government of the Slovak Republic. The three levels of education are fully harmonized with the Bologna principles. The Accreditation Committee of the Government of the Slovak Republic describes very detailed aims of a public health education program including recommended study subjects. Universities add to additional, mostly clinical medicine or hygiene subjects to recommend study subjects leaving likely very little time for research at universities. Conclusions: Despite large progress further effort is needed to clarify what is public health, what kind of subject should be included in curricula and on introduction of public health research at universities.